2007
DOI: 10.1088/0029-5515/47/9/007
|View full text |Cite
|
Sign up to set email alerts
|

Gas balance and fuel retention in fusion devices

Abstract: The evaluation of hydrogenic retention in present tokamaks is of crucial importance to estimate the expected tritium (T) vessel inventory in ITER, limited from safety considerations to 350g. In the framework of the European Task Force on Plasma Wall Interaction (EU TF on PWI) efforts are underway to investigate gas balance and fuel retention during discharges, and to compare the data obtained with those from post-mortem analysis of in-vessel components exposed over whole experimental campaigns. This paper summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
110
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 32 publications
6
110
1
1
Order By: Relevance
“…A slight decrease indicate that the wall pumping is less at the end of the flat top. A similar behavior is found in gas balances for JET [24], but it is unclear, if it is possible to saturate a carbon wall completely. Typically 5 * 10 21 at/s are retained during a high density discharge.…”
Section: Gas Balance With Carbon Wallsupporting
confidence: 65%
“…A slight decrease indicate that the wall pumping is less at the end of the flat top. A similar behavior is found in gas balances for JET [24], but it is unclear, if it is possible to saturate a carbon wall completely. Typically 5 * 10 21 at/s are retained during a high density discharge.…”
Section: Gas Balance With Carbon Wallsupporting
confidence: 65%
“…Dots: Experimental data; Line: SIMNRA simulation; Arrows: Depth of origin of protons with the given energy. Bottom: Deuterium depth pro le including error bars using a tungsten density of 19.3 g/cm 3 . Applied doses of 3 He + : 690 keV 10 µC; 800 keV 5 µC; 2500 keV 5 µC; 4000 keV 5 µC.…”
Section: Discussionmentioning
confidence: 99%
“…Deuterium can penetrate in these materials up to depths of several tens to several hundreds of µm, where it is trapped at low concentrations [1,2]. It has been assumed that this deep penetration is an important process for the deuterium inventory in the tokamak Tore Supra [3], and it has been shown that deep penetration is dominating the remaining deuterium inventory in the all-tungsten tokamak ASDEX Upgrade [4]. In carbon materials this penetration is related to the porosity of the material, while in tungsten the di usion process is driven by the stress-eld induced by implanted deuterium [2].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that this di erence may be explained by deep di usion of D into carbon bre composite (CFC) material [32,33]. This deep di usion has been shown experimentally in laboratory experiments [34].…”
Section: Deuterium Inputmentioning
confidence: 91%